Pengaruh Penambahan Bungkil Kedelai Terproteksi Terhadap Total Solid Dan Berat Jenis Susu Sapi Friesian Holstein Fase Laktasi Awal - Sahawaludin, Risqi; Rimbawanto, Efka Aris; Astuti, Triana Yuni (ANGON: Journal of Animal Science and Technology, 2019)
Background. This study was conducted to determine the effect of supplementation protected soybean meal to total solid and density of early lactation dairy cows. Materials and methods. Ten early lactation Friesian Holstein cows were divided into two groups. Five animals were used as a control group and another groups as treatment object. The feed is forages and concentrates. The control group getting just concentrates, while the treatment group getting concentrate with protected soybean meal as much as 60 g/? milk production. The data obtained were analyzed using T-test analysis. Results. Result showed total solid content between control and tretment group were significant (P<0,05), while density content control and tretment group were not significant (P>0,05). Conclusion. Supplementation protected soybean meal of early lactation dairy cows decrease density content, and increase total solid content.